Especies de periconia sobre las semillas de arroz (Oryza sativa L.) - Sandoval Ramirez, I.=700 1 Lopez, M.O.; Bonilla Bernal, T.
(Es, En)
Ilus., 7 ref.
Keywords: ORYZA SATIVA; PERICONIA; ENFERMEDADES FUNGOSAS; SEMILLAS; CUBA